2011
DOI: 10.5039/agraria.v6i2a939
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de sementes de soja tratadas com inseticidas e submetidas a diferentes períodos de armazenamento

Abstract: Desempenho de sementes de soja tratadas com inseticidas e submetidas a diferentes períodos de armazenamento RESUMOO presente trabalho teve como objetivo avaliar o desempenho fisiológico de sementes de soja armazenadas sob tratamento com inseticidas. Para tanto, as sementes de soja da cultivar M-SOY 6101 foram submetidas a quatros períodos de armazenamento (0, 3, 5 e 7 dias após o tratamento) e sete inseticidas. O delineamento experimental foi o inteiramente casualizado, em esquema fatorial 4 x 7, com quatro re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 7 publications
2
14
1
5
Order By: Relevance
“…In contrast, Dan et al (2011) observed that the treatment of soybean seeds with the insecticides thiamethoxam and fipronil promoted adequate levels of germination and vigor, but with a short period of storage, seven days. Grisi et al (2009) also did not find any change in the vigor and emergence of sunflower seeds treated with thiamethoxam and fipronil.…”
Section: Resultsmentioning
confidence: 60%
“…In contrast, Dan et al (2011) observed that the treatment of soybean seeds with the insecticides thiamethoxam and fipronil promoted adequate levels of germination and vigor, but with a short period of storage, seven days. Grisi et al (2009) also did not find any change in the vigor and emergence of sunflower seeds treated with thiamethoxam and fipronil.…”
Section: Resultsmentioning
confidence: 60%
“…On the other hand, Tavares et al (2007) did not observe differences in germination nor vigor of soybean seeds treated with different doses of thiamethoxam. Similarly, Barros et al (2001) and Dan et al (2011), in their works with beans and soybeans, respectively, verified that the germination of seeds treated with thiamethoxam did not differ in relation to the control treatment.…”
Section: Resultsmentioning
confidence: 94%
“…De forma semelhante, Dan et al (2011) observaram que o tratamento com inseticidas, em sementes de soja, promove adequados níveis de germinação e vigor, durante o período de armazenamento sete dias.…”
Section: Resultsunclassified